A new species in the lichen genus Vahliella from the Canary Islands, including a key to Vahliellaceae, Pannariaceae, and Coccocarpiaceae in Macaronesia - Pérez-Vargas, Israel Pérez-Vargas; Hernández-Padrón, Consuelo; de Paz, P. L. Pérez; van Den Boom, P. P. G.; Jørgensen, P. M. (Phytotaxa, 2014)
Vahliella isidioidea, found on consolidated soil in the laurel forest from the Canary Islands is described as new to science. A description of the species is given together with notes on its chemistry, distribution, ecology and taxonomy. Possible related lichen taxa are discussed briefly and a key to the Macaronesian species of Vahliella and morphologically related species is also provided.